SUN-743 Understanding the Role of Pancreas and Testis Specific lncRNA86 in Estrogen-Dependent Signaling in Breast Cancer - Ramos, Enrique Ivan (J Endocr Soc, 2020)
Long noncoding RNAs (lncRNAs) are emerging as key regulators of diverse cellular processes, but their roles in breast cancer biology are just beginning to be elucidated. In this study, integration of powerful techniques, RNA-seq data from subcellular fractionated RNA with GRO-seq data has yielded a comprehensive catalog of estrogen-regulated lncRNAs in MCF-7 cells. Analysis of RNA-seq data from samples representing molecular subtypes of breast cancer and normal tissue types, revealed that many lncRNAs (such as lincRNA86) show distinct expression patterns. LincRNA86 shows highest normal expression in pancreas followed by testis in normal human tissues. The hypothesis is lincRNA86 regulate estrogen-dependent signaling in breast cancer. In functional assays, knockdown of lncRNA86 inhibits the growth of ER-positive breast cancer cells. Amplified expression of lncRNA86 in breast cancer correlates with clinical outcome. LncRNA86 have now been fully annotated (transcription start and stop site, 5’ cap, polyA tail, and exon/intron structure), and cloned. We are now performing detailed molecular analyses to better understand the underlying mechanisms of action of the lncRNA. We are also currently have experiments underway to view cancer phenotypes: estrogen-dependent tumor growth. Collectively, our preliminary results suggest that lincRNA86 plays a critical role in ERα-dependent pathways.